STUDENTS’ PERCEPTION ON THE USE OF YOUTUBE IN ENGLISH LANGUAGE LEARNING DURING PANDEMIC IN WIRALODRA UNIVERSITY - Natalia Anggrarini; Ikhbal Faturokhman (JELLT (Journal of English Language and Language Teaching), 2021)
The Indonesian Minister of Education and Culture has instructed schools to carry out online learning since March 17, 2020 along with widespread COVID-19. Among all online learning media, YouTube has become increasingly popular for learning tools, especially with young adults. Thus, this research tried to investigate the students’ perception of using YouTube in the study of English skills class. The qualitative approach with case study design was implemented to six undergraduate students of the 3rd semester who voluntarily participated in this research. The instruments used in this research are questionnaires and interviews. The data was analyzed descriptively to answer the research question. The finding reported that YouTube videos make students happy to learn English; it helps them understand the material. However, youtube makes communication with lecturers and classmates difficult without Whatsapp. In terms of strengths and weaknesses, Youtube can keep the students from feeling bored; they can study anytime and anywhere, they can also re-watch the video at will. However, YouTube videos can be a poor learning media if the videos are too long. Youtube is considered expensive without Wi-Fi access. Then the last is the possibility of signal interference.